Brachytherapy structural shielding calculations using Monte Carlo generated, monoenergetic data. Issue 4 (20th March 2014) - Zourari, K.; Peppa, V.; Ballester, Facundo; Siebert, Frank‐André; Papagiannis, P.
Abstract : Purpose: : To provide a method for calculating the transmission of any broad photon beam with a known energy spectrum in the range of 20–1090 keV, through concrete and lead, based on the superposition of corresponding monoenergetic data obtained from Monte Carlo simulation. Methods: : MCNP5 was used to calculate broad photon beam transmission data through varying thickness of lead and concrete, for monoenergetic point sources of energy in the range pertinent to brachytherapy (20–1090 keV, in 10 keV intervals). The three parameter empirical model introduced by Archer et al. ["Diagnostic x‐ray shielding design based on an empirical model of photon attenuation, " Health Phys. 44, – (1983)] was used to describe the transmission curve for each of the 216 energy‐material combinations. These three parameters, and hence the transmission curve, for any polyenergetic spectrum can then be obtained by superposition along the lines of Kharrati et al. ["Monte Carlo simulation of x‐ray buildup factors of lead and its applications in shielding of diagnostic x‐ray facilities, " Med. Phys. 34, 1398–1404 (2007)]. A simple program, incorporating a graphical user interface, was developed to facilitate the superposition of monoenergetic data, the graphical and tabular display of broad photon beam transmission curves, and the calculation of material thickness required for a given transmission from these curves. Results: : Polyenergetic broad photon beam transmission curves of this work, calculated from the superposition of monoenergetic data, are compared to corresponding results in the literature. A good agreement is observed with results in the literature obtained from Monte Carlo simulations for the photon spectra emitted from bare point sources of various radionuclides. Differences are observed with corresponding results in the literature for x‐ray spectra at various tube potentials, mainly due to the different broad beam conditions or x‐ray spectra assumed. Conclusions: : The data of this work allow for the accurate calculation of structural shielding thickness, taking into account the spectral variation with shield thickness, and broad beam conditions, in a realistic geometry. The simplicity of calculations also obviates the need for the use of crude transmission data estimates such as the half and tenth value layer indices. Although this study was primarily designed for brachytherapy, results might also be useful for radiology and nuclear medicine facility design, provided broad beam conditions apply.